Makdonaldyzacja polskiego systemu edukacyjnego - Welskop, Wojciech (Studia Edukacyjne, 2020)
McDonaldization is present in many areas of social life and its various attributes like efficiency,calculability, predictability, and control determine the rhythm of human activity in society. The purpose of this paper is to analyze the educational system in Poland from the perspective of the McDonaldization phenomenon, thereby drawing attention to the role of the consumer culture in the fieldof education and to show the progress of the globalization process and its side effects in this field.